2018
DOI: 10.7567/jjap.57.04fg04
|View full text |Cite
|
Sign up to set email alerts
|

A transient simulation approach to obtaining capacitance–voltage characteristics of GaN MOS capacitors with deep-level traps

Abstract: In this study, GaN MOS capacitance-voltage device simulations considering various interface and bulk traps are performed in the transient mode. The simulations explain various features of capacitance-voltage curves, such as plateau, hysteresis, and frequency dispersions, which are commonly observed in measurements of GaN MOS capacitors and arise from complicated combinations of interface and bulk deep-level traps. The objective of the present study is to provide a good theoretical tool to understand the physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The observed frequency dispersion in the accumulation region lower than −1 V is usually attributed to the high series resistance of p-GaN rather than the interface state [17]. By neglecting the non-ideal effect arises from the difference between the work functions of metal and semiconductor due to variation in the doping level of semiconductor mat erial and oxide trapped charge, the fixed charge density The interface state density (D it ) distribution is evaluated using the Terman method by comparing the experimental C-V curves to the simulated ideal ones at high frequency [18].…”
Section: Resultsmentioning
confidence: 99%
“…The observed frequency dispersion in the accumulation region lower than −1 V is usually attributed to the high series resistance of p-GaN rather than the interface state [17]. By neglecting the non-ideal effect arises from the difference between the work functions of metal and semiconductor due to variation in the doping level of semiconductor mat erial and oxide trapped charge, the fixed charge density The interface state density (D it ) distribution is evaluated using the Terman method by comparing the experimental C-V curves to the simulated ideal ones at high frequency [18].…”
Section: Resultsmentioning
confidence: 99%
“…The authors have already reported a modeling method based on device simulation. 32,33) However, device simulation is a general-purpose physical modeling tool, and heavy resources are required for calculating time and input data creation.…”
Section: Introductionmentioning
confidence: 99%